2023
DOI: 10.5009/gnl220409
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis but Not Fibrosis Is Independently Associated with Poor Outcomes in Patients with Inflammatory Bowel Disease

Abstract: Background/Aims Increased prevalence of nonalcoholic fatty liver disease (NAFLD) and inflammatory bowel disease (IBD) has been reported. However, the effects of NAFLD on the outcome of IBD remains unclear. We investigated whether the presence of NAFLD could influence the outcomes of patients with IBD. Methods We recruited 3,356 eligible patients with IBD into our study between November 2005 and November 2020. Hepatic steatosis and fibrosis were diagnosed using hepatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Bessissow reported a prevalence of 2.2% in IBD defined as FIB-4 of ≥2.67 [29]. A recent study in Korea reports a prevalence of 5.3% in IBD with FIB-4 of ≥1.45 [21]. Ritaccio reported that 16% of patients had progressed to a NFS during 5-year follow-ups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bessissow reported a prevalence of 2.2% in IBD defined as FIB-4 of ≥2.67 [29]. A recent study in Korea reports a prevalence of 5.3% in IBD with FIB-4 of ≥1.45 [21]. Ritaccio reported that 16% of patients had progressed to a NFS during 5-year follow-ups.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies addressed the prevalence of MAFLD in IBD in the Asia-Pacific region (Table 5). The MAFLD prevalence was 10.7% in patients with IBD in China, 16.7% in patients with IBD in South Korea, and 21.8% in CD patients in Japan [19][20][21]. The discordance of prevalence was affected by the measurement methods and regional differences.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, although IBD seems to increase the risk of liver disease progression, a Korean study highlighted how only hepatic steatosis but not fibrosis is associated with poor clinical outcomes. More specifically, the authors found that liver steatosis increased the risk of IBD relapse (defined as IBD-related hospitalizations or surgical interventions or the need to start treatments with corticosteroids, immunosuppressors, or biologic drugs) while fibrosis did not, both in CD and UC [ 9 ]. Therefore, the link between IBD and NAFLD appears to be even more complex, and the real burden of hepatic steatosis on IBD morbidity needs to be better defined.…”
Section: Nafld Clinical Course In Ibd Patientsmentioning
confidence: 99%
“…In a recent systematic review analyzing the impact of NAFLD on IBD-related hospitalization outcomes, Boustany et al highlighted how NAFLD may be related to worse outcomes in individuals with IBD, despite the low quality of available data [ 8 ]. In addition, in a recently published study, Hyun et al estimated the presence of liver steatosis by calculating the Hepatic Steatosis Index (HSI) and Fibrosis-4 (FIB-4) in a cohort of 3356 IBD patients and found that steatosis was associated with increased risk of clinical relapse both in UC and CD patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 52 Moreover, the presence of MASLD (steatosis, but not fibrosis) might increase the risk of an IBD flare. 53 Despite these recent clinical observations, the origin of such observations remains unclear, but could involve gut microbial aspects along the gut-liver axis as reported for other liver diseases. 54 As for obesity, it remains understudied if MASLD and IBD affect the natural course of both diseases and related complications.…”
Section: Clinical Link Between Metabolic Disorders and Ibdmentioning
confidence: 99%